2020
DOI: 10.1007/s00018-020-03540-9
|View full text |Cite
|
Sign up to set email alerts
|

Dysregulated signalling pathways in innate immune cells with cystic fibrosis mutations

Abstract: Cystic fibrosis (CF) is one of the most common life-limiting recessive genetic disorders in Caucasians, caused by mutations in the cystic fibrosis transmembrane conductance regulator (CFTR). CF is a multi-organ disease that involves the lungs, pancreas, sweat glands, digestive and reproductive systems and several other tissues. This debilitating condition is associated with recurrent lower respiratory tract bacterial and viral infections, as well as inflammatory complications that may eventually lead to pulmon… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
41
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 56 publications
(50 citation statements)
references
References 210 publications
(288 reference statements)
1
41
0
1
Order By: Relevance
“…Chronic, progressive low-grade inflammation promoted by NF-κB can cause premature aging (Jurk et al, 2014). CF airway inflammation is associated with excessive production of NF-κBdependent inflammatory mediators such as interleukin-1β (IL-1β), IL-6, IL-8, and TGF-β1, neutrophil recruitment, and decreased response to interferon (IFN)-γ as well as further abnormalities in various signaling pathways (Nichols et al, 2008;Harris et al, 2009;Peterson-Carmichael et al, 2009;Lara-Reyna et al, 2020). The profibrotic cytokine TGF-β is considered a pro-aging factor and is associated with accelerated lung function decline in CF patients (Arkwright et al, 2000).…”
Section: Altered Cellular Communicationmentioning
confidence: 99%
“…Chronic, progressive low-grade inflammation promoted by NF-κB can cause premature aging (Jurk et al, 2014). CF airway inflammation is associated with excessive production of NF-κBdependent inflammatory mediators such as interleukin-1β (IL-1β), IL-6, IL-8, and TGF-β1, neutrophil recruitment, and decreased response to interferon (IFN)-γ as well as further abnormalities in various signaling pathways (Nichols et al, 2008;Harris et al, 2009;Peterson-Carmichael et al, 2009;Lara-Reyna et al, 2020). The profibrotic cytokine TGF-β is considered a pro-aging factor and is associated with accelerated lung function decline in CF patients (Arkwright et al, 2000).…”
Section: Altered Cellular Communicationmentioning
confidence: 99%
“…As reviewed by Lara-Reyna et al (2020) , several immune cell types, including neutrophils, monocytes, and macrophages, are profoundly affected by the loss of CFTR function. As specific examples, the absence of CFTR appears to (i) shift neutrophils and macrophages into a more activated state ( Adib-Conquy et al, 2008 ; Zhang et al, 2018 ), (ii) augment both basal and stimulated cytokine release ( Bonfield et al, 2012 ; Zhang et al, 2018 ; Lara-Reyna et al, 2020 ), (iii) hamper infection resolution ( Bonfield et al, 2012 ), and (iv) impair the production of agents that destroy phagocytosed pathogens (e.g., hypochlorous acid and reactive oxygen species; Zhou et al, 2013 ; Zhang et al, 2018 ). A common thread across these traits is that CFTR serves a strong anti-inflammatory role in multiple immune cell types.…”
Section: Cftr and Immune Responsesmentioning
confidence: 99%
“…Of the many effects TNF signaling has, one intriguing effect is a broad downregulation of cystic fibrosis transmembrane conductance regulator (CFTR) expression in multiple tissues, most notably, in the lung and brain ( Meissner et al, 2012 ; Yagi et al, 2015 ). CFTR is widely expressed in many critical organs, including the lung, brain, heart, kidney, gut, pancreas, immune cells, and blood vessels ( Meissner et al, 2012 ; Yagi et al, 2015 ; Castellani and Assael, 2017 ; Lidington et al, 2019 ; Lara-Reyna et al, 2020 ): it is therefore tempting to propose that reduced CFTR activity mediates several deleterious TNF effects. This would place CFTR-modifying therapeutics in a prime position to alter the course and severity of the COVID-19 pathology.…”
Section: Introductionmentioning
confidence: 99%
“…A recent comprehensive article summarizes the role of dysfunctional CFTR in the controlling cellular signaling pathways used by innate immune cells for combating infections such as airway epithelial cells, neutrophils, monocytes, and macrophages [ 59 ]. Additionally, we and others have shown a clear role of membrane-CFTR in regulating the function of adaptive immune cells, such as CD3+ T cells, CD4+ T cells, CD4+FoxP3+ regulatory T cells (T regs), and B cells [ 59 ].…”
Section: Introductionmentioning
confidence: 99%
“…A recent comprehensive article summarizes the role of dysfunctional CFTR in the controlling cellular signaling pathways used by innate immune cells for combating infections such as airway epithelial cells, neutrophils, monocytes, and macrophages [ 59 ]. Additionally, we and others have shown a clear role of membrane-CFTR in regulating the function of adaptive immune cells, such as CD3+ T cells, CD4+ T cells, CD4+FoxP3+ regulatory T cells (T regs), and B cells [ 59 ]. A recent intriguing study found that CFTR dysfunction in platelets leads to aberrant transient receptor potential cation channel subfamily C member 6 (TRPC6)-dependent platelet activation, which was proposed as a major driver of CF-lung inflammation and impaired bacterial clearance [ 60 ].…”
Section: Introductionmentioning
confidence: 99%